Greed & grievance : economic agendas in civil wars - Berdal, Mats R.( 1965-); Malone, David( 1954-); International Peace Academy (Boulder, Colo.: Lynne Rienner Publishers, 2000)
"This volume identifies the economic and social factors underlying the perpetuation of civil wars, exploring as well the economic incentives and disincentives available to international actors seeking to restore peace to war-torn societies." "The authors consider the economic rationality of conflict for belligerents, the economic strategies that elites use to sustain their positions, and in what situations elites find war to be more profitable than peace. They strive consistently for policy relevance in both their analysis and their prescriptions."--BOOK JACKET.
Incentives and disincentives for violence / David Keen -- Shadow states and the political economy of civil wars / William Reno -- Globalization, transborder trade, and war economies / Mark Duffield -- Doing well out of war: an economic perspective / Paul Collier -- The resource curse: are civil wars driven by rapacity or paucity? / Indra de Soysa -- The view from below / Musifiky Mwanasali -- Arms, elites, and resources in the Angolan civil war / Virginia Gamba and Richard Cornwell -- Targeted financial sanctions / Samuel D. Porteous -- Aiding or abetting? Humanitarian aid and its economic role in civil war / David Shearer -- Shaping agendas in civil wars: can international criminal law help? / Tom Farer.
"A project of the International Peace Academy."
Conference papers.
Includes bibliographical references (p. 235-238) and index.
Keywords: Civil war -- -- Economic aspects; War -- -- Economic aspects; Profiteering; Guerre civile -- -- Aspect économique.; Guerre -- -- Aspect économique.; Profits illicites; Burgeroorlogen; Economische aspecten; Sociale conflicten